2014
DOI: 10.1371/journal.pmed.1001674
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Implementation Strategy in Scaling Up Xpert MTB/RIF for Diagnosis of Tuberculosis in the Indian Health-Care System: A Transmission Model

Abstract: Using a modelling approach, David Dowdy and colleagues investigate how different implementation strategies for Xpert MTB/RIF within the complex, fragmented healthcare system of India may affect tuberculosis control. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 41 publications
(65 reference statements)
0
36
0
Order By: Relevance
“…Cost-effectiveness of Xpert testing at lower-volume centers could potentially be improved with increased volume of patients referred for testing, such as through facility-based screening and other intensified case-finding initiatives. 27,28 Alternatively, referral networks could be further developed to deliver sputum specimens efficiently to more centralized sites, 29,30 an approach which must consider quality of available transport networks and potential for pre-treatment loss to follow-up while awaiting results. Novel lower-cost platforms for Xpert testing (e.g., Xpert Omni, 31 Alere q 32 ) may also aid in cost-effective decentralization of testing.…”
Section: Discussionmentioning
confidence: 99%
“…Cost-effectiveness of Xpert testing at lower-volume centers could potentially be improved with increased volume of patients referred for testing, such as through facility-based screening and other intensified case-finding initiatives. 27,28 Alternatively, referral networks could be further developed to deliver sputum specimens efficiently to more centralized sites, 29,30 an approach which must consider quality of available transport networks and potential for pre-treatment loss to follow-up while awaiting results. Novel lower-cost platforms for Xpert testing (e.g., Xpert Omni, 31 Alere q 32 ) may also aid in cost-effective decentralization of testing.…”
Section: Discussionmentioning
confidence: 99%
“…These dynamic models have linked transmission models to economic models to predict the costeffectiveness of specific intervention strategies. 40,41 One study examined the estimated incidence of new and retreatment cases in countries with a high tuberculosis burden, and concluded that more than 95% of MDR tuberculosis is due to primary transmission of resistant strains. 42 Consistent with the results described above, these findings suggest that a focus on early detection and improved treatment of MDR tuberculosis is needed to curtail future incidence.…”
Section: Modelling Mdr Epidemicsmentioning
confidence: 99%
“…Worse still, if most transmissions occur in the first 10 months, then even a perfect diagnostic test at the health facility could not avert those events. Thus, the dynamic trajectories of transmission, health-care seeking and diagnostic index of suspicion over the course of TB disease are inextricably linked to the epidemiological impact of novel diagnostic tests 19,[30][31][32][33] -and overly simple depictions of those trajectories may systematically overestimate that impact. Adding complexity to these simple frameworks requires additional data to inform a more nuanced understanding of the impact of diagnostic tests.…”
mentioning
confidence: 99%